Amgen : launching Repatha - Calkins, Tim; Harris, Mike (London : Kellogg School of Management, 2017)
In March 2015, Amgen is preparing for the launch of Repatha, a new molecule that has demonstrated a remarkable ability to treat high cholesterol. Through a series of clinical trials, Amgen has proven that the molecule is both safe and effective for patients with high cholesterol. It also is effective for patients with familial hypercholesterolemia, a difficult-to-treat population that has exceptionally high levels of cholesterol. Amgen expects the FDA to approve the molecule before the end of the year. Now, the Repatha team has to develop a revenue forecast.
Originally published in Calkins, T., & Harris, M. (2017). Amgen: Launching Repatha. 5-416-759. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Amgen Inc; Heart -- Diseases -- Treatment -- United States; Hypercholesteremia